Philosophical & bioethical boundaries in current biotechnologies: human enhancement and welfare biology - Fernández-Mateo, Joaquín (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
The aim of this paper is to conduct a descriptive and normative exploration of the most intriguing current biotechnologies. Firstly, biotechnological means capable of enhancing humans will be described, including the possibility of transferring the mind to a non-biological device. Secondly, the emerging discipline of welfare biology will be explored, subjecting it to a theoretical stress test. Well-founded concerns regarding the potential impact of biotechnologies exist, with a particular emphasis on the speculative nature of mind uploading. In contrast to large-scale welfare biology, small-scale welfare biology seems entirely plausible to reduce wild animal suffering.